Border militarisation and the re‐articulation of sovereignty. Issue 2 (11th February 2016) - Jones, Reece; Johnson, Corey
Abstract : This paper identifies a global trend towards hardened, militarised borders through the use of military technologies, hardware and personnel. In contrast to claims of waning state sovereignty, drawing on detailed case studies from the United States and European Union, we argue the militarisation of borders represents a re‐articulation and expansion of state sovereignty into new spaces and arenas. We argue that the nexus of military‐security contractors, dramatically increased security budgets, and the discourse of threats from terrorism and immigration is resulting in a profound shift in border security. The construction of barriers, deployment of more personnel and the investment in a wide range of military and security technologies from drones to smart border technologies that attempt to monitor, identify and prevent unauthorised movements are emblematic of this shift. We link this increasing militarisation to dehumanisation of migrant others and to the increasing mortality in border spaces. By documenting this trend and identifying a range of different practices that are included under the rubric of militarisation, this paper is both a call for nuanced interpretation and more sustained investigation of the expansion of the military into the policing of borders.